Guest-dependent negative thermal expansion in a lanthanide-based metal–organic framework. Issue 35 (12th August 2019) - Gładysiak, Andrzej; Moosavi, Seyed Mohamad; Sarkisov, Lev; Smit, Berend; Stylianou, Kyriakos C.
Abstract : A lanthanide-based metal–organic framework (MOF) namedSION-2, displays strong and tuneable uniaxial negative thermal expansion (NTE). Abstract : A lanthanide-based metal–organic framework (MOF) namedSION-2 displays strong and tuneable uniaxial negative thermal expansion (NTE). The coefficient of thermal expansion α 1 reaches −153(6) MK −1 between 100 and 340 K, which is the highest value reported to date for Ln-based MOFs. After heating to 380 K and subsequent cooling, the directionality and the magnitude of the effect change dramatically: the strong NTE effect is no longer observed along X 1, while a much weaker NTE effect emerges in a perpendicular direction. Loss of non-coordinated N, N -dimethylformamide molecules together with the reduction of the size of structural voids stands as a rationale behind this switch-over.